Optimal strategies for sampling functional traits in species-rich forests - Paine, C. E. Timothy (2015)
1. Functional traits provide insight into a variety of ecological questions, yet theoptimal sampling method to estimate the community-level distribution of plantfunctional trait values remains a subject of debate, especially in species-rich forests.2. We present a simulation analysis of the trait distribution of a set of nine completelysampled permanent plots in the lowland rain forests of French Guiana.3. Increased sampling intensity consistently improved accuracy in estimatingcommunity-weighted means and variances of functional trait values, whereas therewas substantial variation among functional traits, and minor differences amongsampling strategies.4. Thus, investment in intensified sampling yields a greater improvement in theaccuracy of estimation than does an equivalent investment in sampling designcomplication.5. Notably, ?taxon-free? strategies frequently had greater accuracy than did abundancebasedstrategies, which had the additional cost of requiring botanical surveys.6. We conclude that there is no substitute for extensive field sampling to accuratelycharacterize the distribution of functional trait values in species-rich forests.